Yoga Gymnology of Process Involution Uterus Mom Post-Partum - Sunarsih, Sunarsih; Astuti, Titi (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
Post-partum haemorrhage is the main cause of maternal morbidity and mortality, among others, due to the failure of the uterine involution process, which is influenced by physical and psychological adaptations, marked by hormonal changes. Attempts are made with yoga exercises so that post-partum mothers focus on physical exercise, breathing, muscle strengthening pelvic floor and relaxation. Data obtained by researchers in the working area of the long inpatient health centre in Bandar Lampung, it is known that in 2019 the number of post-partum mothers was 754 people. From the results of the interview, it was found that 8 (80%) mothers had never been taught yoga exercises to accelerate uterine involution. Nursing care for post-partum mothers given only standards from the Ministry of Health. The purpose of this study is to know the effect of yoga exercises on uterine involution in the working area of the long inpatient health centre in Bandar Lampung. This study using a quantitative design with an analytical design using a Quasi-experimental approach with one group pre-posttest design. The research site will be carried out in the work area of the Puskesmas inpatient Bandar Lampung. In this study, the researchers identified the sample used as 60 post-partum mothers as respondents. Then the researchers determined the sample based on the researchers' own considerations according to the desired criteria. Divided into 30 post-partum mothers in the intervention group and 30 post-partum mothers in the control group. The sampling method used was the purposive sampling technique. The study used a t-test (t-test). The results obtained were based on statistical tests, there was a difference in uterine involution in the intervention group and control with p-value = 0.000, the result was the effect of yoga gymnastics on uterine involution in post-partum mothers in the Puskesmas Panjang p-value. 0.000 less than 0.005 means that there is an effect of yoga exercise on the postpartum uterine involution process. Suggestions from health centre staff for maternity nurses and midwives can provide yoga exercises to post-partum mothers according to the yoga exercise booklet that researchers have provided. Health cadres can work together with post-partum mothers in practising yoga exercises for post-partum mothers.Abstrak: erdarahan post partum merupakan penyebab utama morbiditas dan mortalitas ibu antara lain akibat kegagalan proses involusi uterus yang dipengaruhi oleh adaptasi fisik dan psikis yang ditandai dengan perubahan hormonal. Upaya yang dilakukan dengan latihan yoga agar ibu post partum fokus pada latihan fisik, pernapasan, penguatan otot dasar panggul dan relaksasi. Data yang diperoleh peneliti di wilayah kerja Puskesmas Rawat Inap Lama Bandar Lampung diketahui pada tahun 2019 jumlah ibu nifas sebanyak 754 orang. Dari hasil wawancara diketahui bahwa 8 (80%) ibu belum pernah diajarkan senam yoga untuk mempercepat involusi uterus. Asuhan keperawatan ibu nifas hanya diberikan standar dari Kementerian Kesehatan. Tujuan penelitian ini adalah untuk mengetahui pengaruh senam yoga terhadap involusi uteri di wilayah kerja Puskesmas Rawat Inap lama Bandar Lampung. Dalam penelitian ini menggunakan desain kuantitatif dengan desain analitik menggunakan pendekatan Quasi eksperimen dengan one group pre-post test design. Lokasi penelitian akan dilaksanakan di wilayah kerja Puskesmas Rawat Inap Bandar Lampung. Dalam penelitian ini peneliti mengidentifikasi sampel yang digunakan adalah 60 ibu nifas sebagai responden. Kemudian peneliti menentukan sampel berdasarkan pertimbangan peneliti sendiri sesuai dengan kriteria yang diinginkan. Dibagi menjadi 30 ibu nifas pada kelompok intervensi dan 30 ibu nifas pada kelompok kontrol. Metode pengambilan sampel yang digunakan adalah teknik purposive sampling. Penelitian menggunakan uji t (uji-t). Hasil yang diperoleh berdasarkan uji statistik, terdapat perbedaan involusi uterus kelompok intervensi dan kontrol dengan nilai p = 0,000, hasil penelitian ini adalah pengaruh senam yoga terhadap involusi uterus ibu nifas di Puskesmas Panjang p-value . 0,000 kurang dari 0,005 artinya ada pengaruh senam yoga terhadap proses involusi uteri postpartum. Saran dari petugas Puskesmas agar perawat dan bidan bersalin dapat memberikan senam yoga kepada ibu nifas sesuai dengan booklet senam yoga yang telah peneliti sediakan. Kader kesehatan dapat bekerjasama dengan ibu nifas dalam mempraktekkan senam yoga bagi ibu nifas.